In context Teresa of Ávila, John of the Cross, and their world - O'Keefe, Mark 1956- (Washington, D.C ICS Publications, Institute of Carmelite Studies, 2019)
The Spanish world of the sixteenth century -- The city of Ávila -- Honor, social class, and poverty -- Reform of the Church and religious orders -- The Carmelites -- The Monastery of the Incarnation -- Spiritual antecedents -- Alumbrados -- Jews, conversos, and the Spanish inquisition -- Teresa of Jesus: a woman in sixteenth-century Spain.
"This title investigates the historical and sociohistorical context of Teresa of Ávila and John of the Cross. These two prolific authors, sixteenth-century religious reformers, and Catholic saints collaborated over the span of two decades. Scholar Mark O'Keefe dives deep into various aspects of sixteenth-century Catholic Spain to determine how events, people, places, and trends influenced the work of Teresa and John. Readers will gain a better insight into how the real dangers of the Spanish Inquisition kept these reformers on their toes, careful to appease ecclesiastical censors and the Spanish crown"--
Includes bibliographical references and index
Keywords: Teresa -- of Avila, Saint -- 1515-1582; John of the Cross -- Saint -- 1542-1591; Carmelites -- Spain -- History -- 16th century; Catholic Church -- Spain -- History -- 16th century; Mysticism -- Spain -- History -- 16th century; Monasticism and religious orders -- Spain -- History -- 16th century; Inquisition -- Spain; Spain -- Church history -- 16th century; Avila (Spain) -- Social conditions -- 16th century